MEDIA EXPOSURE INDUCED SECONDARY TRAUMATIC STRESS AMONG UNIVERSITY STUDENTS OF PAKISTAN: ROLE OF PERSONAL VARIABLES - Kanwal, Fareeha; Yousaf, Tahira (Journal of Pakistan Psychiatric Society, 2022)
OBJECTIVE To assess level of Media Exposure Induced Secondary Traumatic Stress (MEISTS) among emerging adults of Pakistan and to explore the role of personal variables of gender, family structure, experiencing a recent primary trauma, socioeconomic status, social support of family and friends, and levels of religiosity as possible contributing factors in this regard STUDY DESIGN Quantitative survey design PLACE AND DURATION OF STUDY The study was conducted from March to August 2021 and the data was collected from public and private universities of Karachi SUBJECTS AND METHODS The sample of 535 university students was collected using non-probability purposive convenient sampling method. 186 (34.8%) were males and 337 (63.0%) were females, age ranging from 18 to 25 years with mean age of 20.62 ± 1.71. Secondary Traumatic Stress Media-Induced Questionnaire and semi-structured interview form were used for data collection. RESULTS Results indicated that that 47.9% of the sample scored low on the overall construct of MEISTS, 44.9% came in moderate range while 4.5% showed high levels of MEISTS. On sub components of MEISTS, on intrusion, 54.0% scored low, 34.2% scored moderate while 9.7% scored high. On avoidance, 32.1% scored low, 57.6% scored moderate and 9.3% scored in high range. On arousal, 37.4% scored low, 51.0% scored moderate and 10.5% scored high. Out of all the personal variables studied, gender, experiencing a recent primary trauma, social support of family, and levels of religiosity showed significant results. CONCLUSION The study indicated that as almost 50% of the sample exhibited MEISTS, measures must be taken in order for people to have better understanding of how media is affecting them.